2015
DOI: 10.4137/ijtr.s19985
|View full text |Cite
|
Sign up to set email alerts
|

The Aryl Hydrocarbon Receptor: A Review of Its Role in the Physiology and Pathology of the Integument and Its Relationship to the Tryptophan Metabolism

Abstract: The aryl hydrocarbon receptor (AHR) is a cytosolic receptor for low molecular weight molecules, of which the most widely recognized ligand is 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), and the most widely recognized effect, chloracne. Adverse effects of manipulation were most recently and graphically demonstrated by the poisoning of Viktor Yushchenko during the Ukrainian presidential elections of 2004. However, recent research has revealed a receptor with wide-ranging, and at times, paradoxical actions. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 121 publications
2
49
0
1
Order By: Relevance
“…The process initiates apoptosis and involves damage to nuclear DNA accompanied by mitochondrial dysfunction 10.1029/2018RG000629 (Frauenstein et al, 2013). There is a general consensus that the AhR of modern humans is implicated in DNA repair (Dittmann et al, 2016;Schreck et al, 2009), tumor suppression (Fan et al, 2010;Yu et al, 2017), epidermal barrier function (Noakes, 2015), skin tanning response, and melanocyte homeostasis (Jux et al, 2011;Luecke et al, 2010). Phylogenetic analysis suggested that the ability of vertebrate AhR to sense xenobiotics was acquired at a late stage of evolution, implying that the driving force for evolutionary conservation of AhR lies not only in its role in xenobiotic metabolism but also in normal cell development (Hahn et al, 2017;Hao & Whitelaw, 2013).…”
Section: The Role Of the Ahrmentioning
confidence: 99%
“…The process initiates apoptosis and involves damage to nuclear DNA accompanied by mitochondrial dysfunction 10.1029/2018RG000629 (Frauenstein et al, 2013). There is a general consensus that the AhR of modern humans is implicated in DNA repair (Dittmann et al, 2016;Schreck et al, 2009), tumor suppression (Fan et al, 2010;Yu et al, 2017), epidermal barrier function (Noakes, 2015), skin tanning response, and melanocyte homeostasis (Jux et al, 2011;Luecke et al, 2010). Phylogenetic analysis suggested that the ability of vertebrate AhR to sense xenobiotics was acquired at a late stage of evolution, implying that the driving force for evolutionary conservation of AhR lies not only in its role in xenobiotic metabolism but also in normal cell development (Hahn et al, 2017;Hao & Whitelaw, 2013).…”
Section: The Role Of the Ahrmentioning
confidence: 99%
“…KYNA, whose mammalian brain concentrations in adulthood are in the nanomolar to low micromolar range, exerts neuroactive properties as an antagonist of the alpha 7 nicotinic acetylcholine (α7nACh) receptors (Hilmas et al, 2001) and N-methyl-D-aspartate (NMDA) receptors (Perkins and Stone, 1982). KYNA also acts as a ligand of G protein-coupled receptor (GPR) 35 and the aryl hydrocarbon receptor (AhR), two signaling receptors that are functional in both the brain and peripheral organs (Divorty et al, 2015; Julliard et al, 2014; Mackenzie and Milligan, 2015; Moroni et al, 2012; Noakes, 2015). The second branch of the KP is predominantly metabolized in microglial cells (Guillemin et al, 2001, 2003; Heyes et al, 1996; Saito and Heyes, 1996), where the enzyme kynurenine 3-monooxygenase (KMO) metabolizes kynurenine to 3-hydroxykynurenine (3-HK), and the downstream catabolite 3-hydroxyanthranilic acid is formed by the enzyme kynureninase.…”
Section: Introductionmentioning
confidence: 99%
“…It serves as a cytosolic ligand-activated transcription factor which, upon ligand binding, translocates into the nucleus, where it dimerizes with the AhR nuclear translocator (ARNT) followed by binding to specific sites in target gene promoters [13]. Much research in the last 15 years has revealed that the AhR is involved in various physiological aspects such as cell homeostasis, cell proliferation and differentiation, embryogenesis, carcinogenesis, inflammation, and host immunity [13,14]. Several reports also indicate an important function of the AhR for maintaining the skin barrier [15,16].…”
Section: Doi: 101159/000492162mentioning
confidence: 99%